Implementasi Kepemimpinan Integratif Berbasis Nilai Profetik: Studi Analitis Gaya Transformasional, Instruksional, dan Servant di SMA Muhammadiyah PK Kottabarat Surakarta - Maheraka, Naufal Aden; Ali, Mohamad (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The principal’s leadership plays a strategic role in determining the direction and quality of educational implementation in schools. This study aims to analyze the implementation of integrative leadership based on prophetic values through the application of transformational, instructional, and servant leadership styles at SMA Muhammadiyah PK Kottabarat Surakarta. Islamic-based schools face challenges in integrating academic excellence with the development of religious character; therefore, a leadership model is required that is not only managerially effective but also morally and spiritually grounded. This research employed a qualitative approach with a field study design. Data were collected through participatory observation, in-depth interviews, and documentation, and were analyzed using interactive analysis techniques with triangulation to ensure data validity. The findings indicate that the integration of transformational, instructional, and servant leadership forms an Islamic Integrative Leadership model that combines a vision for change, the strengthening of learning quality, and the values of service and exemplary conduct within an Islamic framework. Transformational leadership fosters a shared vision and an innovative culture; instructional leadership enhances the quality of the learning process through effective academic supervision; while servant leadership creates a humanistic and participatory school climate. This leadership model contributes to improving teacher professionalism, strengthening students’ character, and establishing a religious school culture oriented toward holistic and sustainable educational quality.